Performance of natural draft hybrid cooling system of large scale steam turbine generator unit. (25th July 2017) - Huang, Yuchen; Chen, Lin; Huang, Xianwei; Du, Xiaoze; Yang, Lijun
Highlights: Iterative procedure for numerical simulations of the hybrid cooling system was introduced. Thermo-flow performance comparison between the dry and hybrid cooling was conducted. Hybrid cooling mode performs better than dry cooling system except for medium wind speeds condition. Performances of dry and wet cooling section have an interaction effect with each other. Abstract: To overcome the shortage of dry cooling technology for large scale steam turbine generator unit in summer, the potential feasibility of hybrid cooling was investigated numerically. The physical model was established for the thermo-flow performances of a hybrid cooling system, which combined the air-cooled heat exchangers and water spray facility in a natural draft cooling tower. The mathematical model included the heat and mass transfer between circulating water and cooling air, as well as the condensation of exhaust steam from turbine. The impacts of cooling modes, operating parameters and ambient conditions of the natural draft hybrid cooling system were investigated accordingly. The results showed that both dry and wet cooling sections determined the thermo-flow performances of hybrid cooling system. Due to the blocking effects of upstream air-flows with medium wind speeds, the hybrid cooling mode may have poorer performance than that of dry cooling system. The large droplet diameter and low spray water flow ratio could deteriorate the thermo-flow performances of hybrid cooling mode, which were even worse than that of dry cooling mode and dry cooling system. The operating parameters obtained and the conditions of cooling mode selection may benefit the future application of the hybrid cooling technology.